An experience in multilingual mathematics teaching - CECCHINI, CARLO; FOGALE, MATTEO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2004)
Can a multilingual approach help mathematical teaching? And can mathematical language be helpful in modifying our feelings about a “minority” language? We will provide a short outline of a short teaching experiment in a high school in a bilingual area (Friulian-Italian), in which we sought to explore some of the opportunities offered by a multilingual approach to mathematical teaching.